Current use and performance of the different fetal growth charts in the Italian population. (September 2020) - Stampalija, Tamara; Ghi, Tullio; Rosolen, Valentina; Rizzo, Giuseppe; Ferrazzi, Enrico Maria; Prefumo, Federico; Dall'Asta, Andrea; Quadrifoglio, Mariachiara; Todros, Tullia; Frusca, Tiziana; ,
Highlights: We report wide discrepancies among the Italian referral centers regarding the fetal growth charts. International growth charts might under-diagnose small for gestational age fetuses. International growth charts might, especially, over-diagnose large for gestational age fetuses. Before implementing new charts, an exploratory analysis is needed. Abstract: Objectives: The choice of growth charts impacts on screening, diagnosis and clinical management of fetal growth abnormalities. The objectives of the study were to evaluate: 1) the clinical practice at a national level among tertiary referral centers in the use of fetal biometric growth charts; and 2) the impact on fetal growth screening of existing national and international growth charts. Study design: A questionnaire was sent to 14 Italian tertiary referral centers to explore biometric reference growth charts used in clinical practice. National and international (Intergrowth-21st and World Health Organization) fetal growth charts were tested on a large national cohort of low risk women with singleton uneventful pregnancy derived from a retrospective cross-sectional multicenter study (21 centers). The percentage of fetuses with biometric measurements below and above the 10th and 90th percentile for each biometric parameter and gestational week were calculated for each growth chart. The percentile curves of the study population were calculated by non-linear quantile regressions. Results: Twelve Italian centers (86 %) answered to the questionnaire showing a wide discrepancy in the use of growth charts for fetal biometry. The cohort included 7347 pregnant women. By applying Intergrowth-21st growth charts the percentage of fetuses with head circumference, abdominal circumference and femur length below the 10th centile was 3.9 %, 3.6 % and 2.3 %, and above the 90th centile 29.9 %, 32.5 % and 46 %, respectively. The percentages for the World Health Organization growth charts for head and abdominal circumferences and femur length were: below the 10th centile 6.3 %, 7.2 % and 5.3 %, and above 90th centile 22.8 %, 21.3 % and 31.9 %, respectively. Conclusions: The wide discrepancy in clinical use of fetal growth charts in Italian centers warrants the adoption of an uniform set of charts. Our data suggest that immediate application into clinical practice of international growth charts might result into an under-diagnosis of small for gestational age fetuses and, especially, in an over-diagnosis of large for gestational age fetuses with major consequences for clinical practice. On these grounds, there is an urgent need for a nationwide study for the prospective evaluation of international growth charts and, if needed, the construction and adoption of methodologically robust national growth charts.